2019
DOI: 10.21273/hortsci13553-18
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Characterization of Greenhouse-grown Lettuce (Lactuca sativa L. ‘Green Towers’) with Applications for Supplemental Lighting Control

Abstract: Plant light use efficiency decreases as light intensity is increased, and a better understanding of crop-specific light responses can contribute to the development of more energy-efficient supplemental lighting control strategies for greenhouses. In this study, diurnal chlorophyll fluorescence monitoring was used to characterize the photochemical responses of 'Green Towers' lettuce (Lactuca sativa L.) to photosynthetic photon flux density (PPFD) and daily light integral (DLI) in a greenhouse during a productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 40 publications
5
25
2
Order By: Relevance
“…The asymptotic increase in ETR with increasing PPFD ( Figure 3 ) also is consistent with previous findings. Weaver and van Iersel [ 7 ] likewise found that ETR of ‘Green Towers’ lettuce responded to PPFD with an exponential rise to a maximum but reported a higher asymptote (121 µmol m −2 s −1 ). Zhen and van Iersel [ 10 ] found that the asymptote of the ETR curve depended on the light intensity plants received prior to the measurements, with plants grown in shade having lower ETR asymptotes than those grown in full sun.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The asymptotic increase in ETR with increasing PPFD ( Figure 3 ) also is consistent with previous findings. Weaver and van Iersel [ 7 ] likewise found that ETR of ‘Green Towers’ lettuce responded to PPFD with an exponential rise to a maximum but reported a higher asymptote (121 µmol m −2 s −1 ). Zhen and van Iersel [ 10 ] found that the asymptote of the ETR curve depended on the light intensity plants received prior to the measurements, with plants grown in shade having lower ETR asymptotes than those grown in full sun.…”
Section: Discussionmentioning
confidence: 99%
“…The Φ PSII decreased linearly as PPFD increased ( Figure 3 ), which is consistent with previous studies. Weaver and van Iersel [ 7 ] reported that the Φ PSII of ‘Green Towers’ lettuce grown and measured in a greenhouse under natural light decreased exponentially as PPFD increased from 0 to ≈1500 µmol m −2 s −1 . These plants were exposed to a wider range of PPFDs than those in the current study, which may explain the differences in trends, linear versus exponential, between the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations